The Tax-Elasticity of Tangible Fixed Assets: Evidence from Novel Corporate Tax Data - Sean Mc Auliffe; Georg U. Thunecke; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper develops a new approach to calculate country-industry-year-specific forward-looking effective tax rates (FLETRs) based on a panel of 19 industries, 221 countries, and the years 2001 to 2020. Besides statutory corporate tax rate and tax base determinants, the FLETRs account for typical country-industry-specific financing structures as well as asset compositions. We show that FLETRs suffer from significant measurement error when the latter information is neglected, owing primarily to inappropriately assigned asset weights to statutory depreciation allowances. Our empirical analysis exploits the substantial variation in FLETRs over time to provide estimates of the tax semi-elasticity of corporate investment in tangible fixed assets. Based on more than 24 million firm-entity observations, our results suggest a statistically significant tax semi-elasticity of -0.41, which is at the lower end of previous findings. We further show that different subgroups of firms respond very heterogeneously to tax incentives.
Keywords: H25; H32; F23; 330; corporate taxation; depreciation allowances; effective marginal tax rates; investment responses; predictive mean matching